2005
DOI: 10.1016/j.cell.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, Oxidants, and Aging

Abstract: The free radical theory of aging postulates that the production of intracellular reactive oxygen species is the major determinant of life span. Numerous cell culture, invertebrate, and mammalian models exist that lend support to this half-century-old hypothesis. Here we review the evidence that both supports and conflicts with the free radical theory and examine the growing link between mitochondrial metabolism, oxidant formation, and the biology of aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
2,943
4
54

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,915 publications
(3,055 citation statements)
references
References 106 publications
54
2,943
4
54
Order By: Relevance
“…We further examined mitochondrial function and structure in DS HF and Dp16 MEF. As the mitochondrial network is the main source of cellular ROS (Balaban et al, 2005) mitochondrial ROS were quantified with a radiometric biosensor (mitoHyPer) that detects peroxide intermediates in the organelle (see methods). Cellular ROS, mitochondrial membrane potential (MMP) and network integrity were also assessed to establish the putative correlation between ROS levels and mitochondrial deficits.…”
Section: Resultsmentioning
confidence: 99%
“…We further examined mitochondrial function and structure in DS HF and Dp16 MEF. As the mitochondrial network is the main source of cellular ROS (Balaban et al, 2005) mitochondrial ROS were quantified with a radiometric biosensor (mitoHyPer) that detects peroxide intermediates in the organelle (see methods). Cellular ROS, mitochondrial membrane potential (MMP) and network integrity were also assessed to establish the putative correlation between ROS levels and mitochondrial deficits.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, an interesting relationship was found between the rate of ROS production during mitochondrial reverse electron transport in vitro and lifespan in vertebrate homeotherms (Lambert et al., 2007). Several reviews have described the mechanisms of ROS production in mitochondria and discussed their potential contribution in aging (Balaban et al., 2005; Brand, 2010). Here, we will only give a brief summary and we will focus on the possible link between ROS production and mPTP opening during aging.…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%
“…This was assigned to the decline in the electron transfer chain capacity, the dysfunction of respiratory complexes, the decrease in ROS scavenging enzymes, and the induction of mutations of mitochondrial DNA, which is susceptible to oxidative damage because it lacks protection from ROS and because of its proximity to them (Balaban et al., 2005; Genova & Lenaz, 2015; Hoppel, Lesnefsky, Chen, & Tandler, 2017; Kwon, Choi, Cho, & Lee, 2015). It was suggested that the accumulation of these mutations in turn deteriorates electron transfer chain function and further increases ROS production, leading to a deleterious vicious cycle.…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria, together with peroxisomes, are the major source of ROS. This metabolic role assigns to these organelles a perhaps crucial function in the determination of lifespan (see Balaban et al 39 for a review). Mitochondrial dynamics seems to play a role in production of ROS as well as in longevity.…”
Section: Function Follows Form: Consequences Of Mitochondrial Shape Cmentioning
confidence: 99%